2010
DOI: 10.1586/erp.09.72
|View full text |Cite
|
Sign up to set email alerts
|

Modeling healthcare expenditures: overview of the literature and evidence from a panel time-series model

Abstract: The rapid growth of healthcare expenditures in the past 40 years in many industrial countries has contributed to an improvement in life expectancy and the quality of life, but has also jeopardized the sustainability of public budgets. For the future, it is important to get more insight into the determinants of this growth. Factors, such as aging, income growth and technological development have been discussed extensively. In this review, we want to pay attention to a somewhat neglected factor: the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Health declines with age so as the number and percentage of older people increases, it is reasonable to expect that, if everything else is held constant, spending on health care will increase. An extensive review of the literature on health care expenditure by van Elk et al (2010) found that "the effect of the population's age structure is usually insignificant". As Uwe Reinhardt observes, "at age 60 or so, health spending per capita rises sharply with age" (Reinhardt, 2008).…”
Section: Causes Of High Health Care Spendingmentioning
confidence: 99%
“…Health declines with age so as the number and percentage of older people increases, it is reasonable to expect that, if everything else is held constant, spending on health care will increase. An extensive review of the literature on health care expenditure by van Elk et al (2010) found that "the effect of the population's age structure is usually insignificant". As Uwe Reinhardt observes, "at age 60 or so, health spending per capita rises sharply with age" (Reinhardt, 2008).…”
Section: Causes Of High Health Care Spendingmentioning
confidence: 99%
“…Health care expenditures are considered to be at least in part influenced by the aging population, but the increase of performing specialised surgical procedures also contributes to high hospital costs. [1][2][3] Post-operative complications also substantially increase the use of additional resources per patient and prolong the hospital stay, raising medical costs even further. [4][5][6][7][8] A pancreatoduodenectomy (PD) is a typical example of a complex, highly specialised surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…These consequences include a greater demand for health services for a large proportion of the population over time and threaten health care systems already at risk from the current economic crisis and social and demographic changes. As a result, experts are searching for new ways to provide better health care services at sustainable costs (Bernal‐Delgado & Ortun‐Rubio, 2010; Brito‐Sanfiel, Diago‐Cabezudo, & Calderón, 2010; Van Elk, Mot, & Franses, 2010).…”
mentioning
confidence: 99%